EMPLOYEE PRIVACY ISSUE SMOKERS' ADVOCATE (Tufts Archival Research Center, 2007)
Smoker’s Advocate Newsletter reporting on employee privacy in the workplace. Argues that employers have no right regulating employees outside of the workplace. Deems decision to fire an employer based on the fact that he might smoke outside the workplace discrimination and thus infringing on civil rights.